SYSTEMATIC LITERATURE REVIEW: LEAN ERGONOMICS ANALYSIS IN SMALL & MEDIUM ENTERPRISES (SMEs) MANUFACTURING SECTOR (Journal of Technology and Operations Management, 2024)
Ergonomics has emerged as a significant workplace issue, negatively impacting finances due to worker absence and reduced productivity. Small and Medium Enterprises (SMEs) are particularly prone to occupational accidents, contributing to over 80% of such incidents. This review delves into the perspective of lean ergonomics within SMEs. The study followed a structured review protocol,formulating research questions and systematically searching the Scopus and WoS databases. The findings reveal several key points: (1) SMEs commonly implement ergonomics principles addressing awkward postures, repetitive movements, manual material handling, hand-wrist postures, excessive reach, grip strength, and prolonged standing; (2) Lean principles such as SMED, 5S, standardized work,TPM, VSM, and kanban positively impact ergonomics; (3) Various ergonomics assessment methods, including REBA, RULA, HFE, JSI, KIM, OCRA, and Shoaf’s model, are recommended for future research and practical application; (4) Ergonomics can underpin lean transformation efforts, with Lean Manufacturing (LM) contributing to reduced ergonomics risks. However, the review identified alimitation in the scope of databases used (WoS and Scopus), suggesting that expanding the range of databases and research keywords could improve future article searches. The study's primary focus serves as a reference point for future researchers and manufacturers interested in lean ergonomics, emphasizing the need for comprehensive approaches to enhance worker safety and productivity through ergonomic and lean practices.